Pneumatosis intestinalis after lung transplantation for pulmonary graft-versus-host disease - Mesaki, Kumi; Sugimoto, Seiichiro; Otani, Shinji; Kurosaki, Takeshi; Miyoshi, Kentaroh; Yamane, Masaomi; Oto, Takahiro (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Pneumatosis intestinalis, which could complicate a spectrum of clinical conditions ranging from benign to life-threatening, is a rarely encountered complication after lung transplantation (LT). We describe two cases in which PI developed as a complication following LT for pulmonary graft-versus-host disease (GVHD) after hematopoietic stem cell transplantation (HSCT). In addition to the long-term immunosuppression administered for pulmonary GVHD, the intense immunosuppression needed after LT might increase the risk of PI in lung transplant recipients after HSCT. Conservative therapy should be considered for the treatment of PI developing after LT.